Evaluasi Pelaksanaan Program Online Assessment Menggunakan Aplikasi Quizizz di Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa - Yahya, Fahmi; Musahrain, Musahrain (Indonesian Publication Center, 2022)
This research aims to analyze the context, input, process and product of the online assessment program using the Quizizz application at the Faculty of Teacher Training and Education (FKIP) Samawa University. This type of research is evaluative research with a qualitative approach and uses the CIPP (Context, Process, Input, Product) evaluation model by Stufflebeam. Data collection techniques using interviews and observations. This data analysis uses data reduction and drawing conclusions. The results of this research indicate that the online assessment program using the Quizizz application at FKIP Samawa University is considered effective and efficient in achieving its objectives. This program can help lecturers carry out online assessments easily and quickly. Students can also take this online assessment easily and comfortably. Using the Quizizz application can save time and costs in program development and implementation.